Perceptions of High School Students Regarding Cyberbullying and Precautions on Coping with Cyberbullying - Karabatak, Songul; Namli, Aysel; Karabatak, Murat (Ieee, 2018)
The aim of this study is to reveal the perceptions of high school students regarding cyberbullying through metaphor analysis. The research data were obtained from 67 high school students in Elazig Province during the academic year of 2017-2018. Qualitative research method was used in the study. In order to collect data students were asked to complete the prompt Cyberbullying is like ... Because .... Both content and descriptive analysis techniques were utilized to analyze the data. In the analysis of the collected data, participants produced 46 valid metaphors about cyberbullying. Based on these metaphorical images, 10 categories were identified. According to findings most of the high school students had negative opinions about cyber bullying but very few of them also had positive opinions about cyberbullying such as pleasure source. At the end of the study, suggestions have been developed for school administrators, teachers and student about coping with cyberbulling.
Lise Ö?rencilerinin Siber Zorbali?a İlişkin Algilari ve Siber Zorbali?a Karşi Alinmasi Gereken Önlemler
6th International Symposium on Digital Forensic and Security (ISDFS) -- MAR 22-25, 2018 -- Antalya, TURKEY
Keywords: cyberbullying; metaphor; high school students